Improving Press Bending Production Quality through Finite Element Simulation: Integration CAD and CAE Approach - Erico Sofyan Chrissandhi; Eko Pujiyanto; Tonny A. Yuniarto (Journal of Engineering, 2024)
Efficient operations and output of outstanding quality distinguish superior manufacturing sectors. The manufacturing process production of bending sheet metal is a form of fabrication in the industry of manufacture in which the plate is bent using punches and dies to the angle of the work design. Product quality is influenced by plate material selection, which includes thickness, type, dimensions, and material. Because no prior research has concentrated on this methodology, this research aims to determine V-bending capacity limits utilizing the press bending method. The inquiry employed finite element analysis (FEA), along with Solidworks was the tool of choice to develop drawings of design and simulations. The ASTM E290 standard guides this study. The software in this package may combine CAD (Computer-Aided Design) and CAE (Computer-Aided Engineering) without requiring extra design applications. This study tested SPCC and SPHC plate materials with five thickness variations. The findings embrace the number of failure risks associated with press bending exhibited on the von Mises stress diagram, which is directly proportional to showing the thickness limit of each material type throughout the bending process. The study's findings lay the groundwork for improving manufacturing quality by lowering the number of faulty goods produced by trial and error. Because the maximum allowable die width is 12 mm, the thickness limit of the press bending process is 2 mm. However, due to the greater intensity of the SPCC material, it has a reduced defect rate compared to SPHC material.